2021
DOI: 10.1186/s13046-021-02139-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of patient-derived ovarian cancer organoids in the study of PARP inhibitors sensitivity and resistance: from genomic analysis to functional testing

Abstract: Epithelial ovarian cancer (EOC) harbors distinct genetic features such as homologous recombination repair (HRR) deficiency, and therefore may respond to poly ADP-ribose polymerase inhibitors (PARPi). Over the past few years, PARPi have been added to the standard of care for EOC patients in both front-line and recurrent settings. Next-generation sequencing (NGS) genomic analysis provides key information, allowing for the prediction of PARPi response in patients who are PARPi naïve. However, there are indeed som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 135 publications
(181 reference statements)
1
8
0
Order By: Relevance
“…The combined clinical trial data confirmed that the chemo-radiotherapy response of the patients was a very close match with the organoid response of the rectal cancer, with an accuracy of 84.43%, a sensitivity of 78.01% and a specificity of 91.97% ( 41 ). Organoids have also successfully predicted the sensitivity of colorectal cancer ( 42 ), gastric cancer ( 43 ), ovarian cancer ( 44 ) and prostate cancer ( 45 ) to drugs. It appears at the present time that extracting samples from patient tumor tissues, creating and culturing organoids, exposing patient-derived tumor organoids to various drugs to find the best drug or drug combination to treat patients, revealing potential weaknesses of individual treatments based on gene mutation profiles and treatment responses of organoids and determining the next treatment route when first-line treatment is ineffective will become the ultimate mode of treatment for cancer ( 46 , 47 ) 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The combined clinical trial data confirmed that the chemo-radiotherapy response of the patients was a very close match with the organoid response of the rectal cancer, with an accuracy of 84.43%, a sensitivity of 78.01% and a specificity of 91.97% ( 41 ). Organoids have also successfully predicted the sensitivity of colorectal cancer ( 42 ), gastric cancer ( 43 ), ovarian cancer ( 44 ) and prostate cancer ( 45 ) to drugs. It appears at the present time that extracting samples from patient tumor tissues, creating and culturing organoids, exposing patient-derived tumor organoids to various drugs to find the best drug or drug combination to treat patients, revealing potential weaknesses of individual treatments based on gene mutation profiles and treatment responses of organoids and determining the next treatment route when first-line treatment is ineffective will become the ultimate mode of treatment for cancer ( 46 , 47 ) 1 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding may have therapeutic significance since it will promote the use of CCDC6 as a biomarker for early-individualized therapy employing targeted treatments. In addition, Patients-Derived Organoids, or PDOs, have also recently been thought to be practical for examining HGSOC's susceptibility to and resistance to PARPi [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cells with HIGH HRD values have been shown to be more sensitive to poly (ADPribose) polymerase (PARPi) inhibitors and platinum therapy [34].…”
Section: Hrd Testingmentioning
confidence: 99%